Assessing the contribution of Islamic finance to economic growth: empirical evidence from Malaysia - Abd majid, M. Shabri; Kassim, Salina (Emerald Group Publishing Limited, 2015)
Purpose– This purpose of this paper is to empirically examine the contribution of the Islamic banking and financial institutions (IBFIs) to economic growth in Malaysia. Design/methodology/approach– Focusing on the post-1997 economic turmoil, the paper relies on several time series tests, such as autoregressive distributed lag (ARDL), vector error correction model (VECM) and variance decompositions (VDCs). Findings– The paper documents significant role played by the IBFIs in Malaysian economy. In particular, significant unidirectional causality was found from the IBFIs development to economic growth, supporting the finance-growth led hypothesis or the supply-leading view. Research limitations/implications– The paper only focuses its analysis on the role of the IBFIs in the Malaysian economy and not the financial sector as a whole. Thus, the findings of this paper are indicative, but inconclusive for the entire financial sector in the country. Practical implications– Continuous efforts should be undertaken to promote the development of the Islamic banking industry due to its significant contribution to Malaysia’s economic growth by further improving the Islamic financial infrastructure, increasing the pool of human capital in the Islamic banking industry, providing conducive legal environment to the IBFIs and maintaining the Islamic financial sector stability. Originality/value– This paper is the first attempt to empirically assess the contribution of Islamic banking institutions in Malaysia using ARDL, VECM and VDCs. KeywordsMalaysia, ARDL, Economic growth, Islamic banking and Islamic financial institutions, Variance decompositions Paper typeResearch paper